Ecotoxicological assessment of engineered nanoparticles in Chironomus riparius - Lopes, Rafael Simões (2015)
Nanoparticles and silver nanoparticles (AgNPs) have been present in natural environments nevertheless new developments have made their presence ubiquitous. They will majorlly be present in waters and sediments with increasing rates as the release to the ecossystems proceeds. Toxicity was assessed and compared in both contaminated water and sediment, the midge species Chironomus riparius was chosen and the toxicity of AgNPs and its ionic counterpart (AgNO3) were analysed and compared. In spiked water the endpoints assessed were: hatching , survival in different stages, larval growth, weight and emergence. Hatching was significantly affected when exposed to AgNPs and AgNO3 spiked water with EC50s values of 3882.27 μg.L-1 and 77.68 ± 6.07 μg.L-1, respectively. First instar mortality in acute exposure had a value of LC50 for AgNPs of 1026.94 μg.L-1 and for AgNO3 of 23.37 μg.L-1. Both head and body length growth rate were unresponsive. Mean time of emergence had an EC50 value of 1289.86 μg.L-1 and EC50 value for emergence the of 843.71 μg.L-1 in regards only to AgNPs.The results for Ag showed that eggs may be a high resistant state in the chironomids life cycle. A critical point of low resistance to water borne contamination is atained during metamorphosis. To evaluate the toxicity of silver compounds when present in sediment endpoints for survival, larval growth, emergence, weight, fertility, sex ratio and biomarkers: catalase, acetylcholinesterase, glutathione-S-transferase and lipid peroxidation were chosen. Growth rates of head and body had an EC50 of 222.62 mg.Kg-1, and 229.84 mg.Kg-1, respectively for AgNPs exposure. Regarding AgNPs exposures, survival of 10 day larvae showed a LC50 of 334.03 mg.Kg-1 and time to emerge a EC50 of 122.19 mg.Kg-1. An increase in activity was only observed in catalase and glutathione s-transferase. The number of egg masses had an EC50 13.10 mg.Kg-1 and their fertility an EC50 of 70.21 mg.Kg-1. Total emergence of adults had EC50 of 49.20 mg.Kg-1 and the time to emergence was significantly affected in the filial generation. Sediment contamination with AgNPs proved to be detrimental to C.riparius with possible intergenerational consequences.